The Effect of Free Cash Flow, Collateralizable Assets, Debt, and Sales Growth on Dividend Policy in Property and Real Estate Companies from 2020-2024 - Siska Refsiana; Novira Sartika (Majapahit Journal of Islamic Finance and Management, 2025)
Dividend policy is one of the important decisions in financial management that reflects a company's strategy in distributing its net income to shareholders. For investors, dividend policy is an important signal regarding the company's financial health and future business growth prospects. This study aims to analyze the effect of free cash flow, collateralizable assets, debt, and sales growth on dividend policy in property and real estate companies listed on the Indonesia Stock Exchange (IDX). This study uses secondary data in the form of annual financial reports obtained through the IDX official website. The sampling method was conducted using purposive sampling based on certain criteria, resulting in 15 companies with a total of 75 observations during the 2020- 2024 period. The data were analyzed using a Partial Least Squares-based Structural Equation Modeling (SEM-PLS) approach with the help of WarpPLS software. The results show that dividend policy is influenced by the company's internal financial condition, particularly related to cash flow flexibility and funding structure, while sales growth is not always in line with an increase in dividend distribution. These findings emphasize the importance of balancing expansion needs and shareholder interests. Therefore, companies are advised to optimize cash flow management and asset structure in determining dividend policy, while investors need to consider fundamental financial factors in making investment decisions wisely and sustainably.